The Effect of SP6 Acupressure and Cinnamon Decoction Combination on Hemoglobin in Dysmenorrhea Adolescents - kamilia, abidatul; Nina Hidayatunnikmah; Nyna PuspitaNingrum (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Dysmenorrhea is a common menstrual pain complaint experienced by adolescent girls. In East Java Province in 2021, around 4,653 adolescents experienced dysmenorrhea, the incidence of primary dysmenorrhea was 4,297 (90.25%). While in Bangkalan around 66.7% experienced dysmenorrhea. Dysmenorrhea can reduce hemoglobin levels due to excessive uterine contractions triggered by prostaglandins. Non-pharmacological therapies such as Sanyinjiao point acupressure (SP6) can stimulate the nervous system and reduce uterine muscle contractions, while cinnamon contains active compounds that are analgesic and anti-inflammatory. Purpose of this study was to determine the effect of the combination of SP6 acupressure and cinnamon decoction on hemoglobin levels in adolescents with dysmenorrhea. Method: uses a one group pretest-posttest design. The study was conducted at the adolescent health post in Karang Asem Village with 32 respondents. The intervention was given twice a day for 5 days of menstruation. Results: showed an increase in hemoglobin levels from an average of 12.20 ± 0.48 gr/dL to 13.75 ± 0.66 gr/dL. The Shapiro-Wilk test showed that the data were normally distributed. The paired t-test produced a p-value of 0.000 (p < 0.05), indicating a significant difference in hemoglobin levels before and after the intervention. Conclusion: is that the combination of SP6 acupressure therapy and cinnamon decoction is effective in increasing hemoglobin levels in adolescents with dysmenorrhea, and can be a practical and safe alternative non-pharmacological treatment.